Paleogene biostratigraphy of Tattapani, Kotli Azad Kashmir, northwest sub-Himalayas, Pakistan - Munir , Munir-ul-Hassan; Baig, Mirza Shahid (Journal of Himalayan Earth Sciences, 2006)
The detailed study of the Paleogene rocks near Tattapani yields 10 age diagnostic benthic larger foraminiferal species. These benthonic foraminiferal species include Operculina patalensis DAVIES and PINFOLD, Miscellanea miscella (d’ARCHIAC and HAIME), Nummulites atacicus (LEYMERIE), Nummulites mamillatus (FICHTEL and MOLL), Assilina subspinosa DAVIES and PINFOLD, Lockhartia tipperi (DAVIES) and Lockhartia conditi (NUTTALL). The analyses of benthic foraminifers suggest that the deposition of the Paleogene sequence occurred in warm and shallow marine environments.